Growth of Corn (Zea mays L.) Treated with Biosaka and Eco enzyme - febriani, syerina febriani; Vauzia; Neli, Pitra (Microbiotech, 2026)
Aim This study aims to determine the effect of biosaka and eco enzyme application on the growth of corn plants (Zea mays L.), as well as to identify the biotic and abiotic factors influencing their growth. Methods The research was conducted using a quantitative method over a period of one month at the Agricultural Extension Center (BPP) in Pariaman City, applying three treatments: control (no treatment), biosaka, and eco enzyme, each with 5 replications. Observed parameters included number of leaves, plant height, and leaf area. Results Biosaka treatment showed the best plant growth compared to control and eco enzyme, with the following average results in the fourth week: Number of leaves: 11.6, Plant height: 64.2 cm, Leaf area: 5.8 cm. This superiority is likely due to the more complete content of nutrients and microorganisms in biosaka. Main conclusions Biosaka is proven to be an effective organic and environmentally friendly alternative to support corn growth and production, although biotic and abiotic factors also contribute to the overall growth outcomes. Key words Eco-Friendly Farming, Corn (Zea mays L.), Biosaka, Eco enzyme